The Relationship Between Knowledge about the Dangers of Cigarettes and Smoking Behavior in Junior High School Students - Nurhasanah, Titi; Kurnia, Sri Indra (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
According to the Global Youth Tobacco Study, adolescent smoking behavior in Indonesia is of great concern. Adolescent smoking behavior has serious consequences, including social, economic, health and even mortality impacts. One of the causes of smoking behavior in adolescents is a lack of understanding about the dangers of smoking. The purpose of this study was to determine the relationship between knowledge about the dangers of smoking and smoking behavior in one of the X Junior High Schools in Sukoharjo Regency. This research design used an analytic observational approach with a cross sectional design. The population studied was all students of SMP X. The sample was taken using simple random sampling technique, obtained a sample of 108 respondents. Data collection was carried out using a questionnaire that had been tested for reliability validity so that the questionnaire was reliable. Data were analyzed using the Chi-square statistical test. The results of statistical tests showed that Ho was rejected with a value of p = 0.003 or p < 0.05, meaning that there is a significant relationship between knowledge about the dangers of smoking with smoking behavior. Researchers suggest that schools socialize the dangers of smoking by providing education to students about the adverse effects of smoking behavior.